2009
DOI: 10.1007/s00442-009-1484-9
|View full text |Cite
|
Sign up to set email alerts
|

Interaction intensity and importance along two stress gradients: adding shape to the stress-gradient hypothesis

Abstract: The stress-gradient hypothesis (SGH) predicts that the community-wide prevalence of positive interactions, relative to negative interactions, is greater under more severe environmental conditions. Because the frequency of positive and negative interactions within a community is the aggregate of multiple pair-wise interactions, one approach to testing the SGH is to examine how pair-wise interactions vary along severity gradients. While the SGH suggests that the net outcome of an interaction should monotonically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
132
3
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(151 citation statements)
references
References 63 publications
(107 reference statements)
8
132
3
1
Order By: Relevance
“…This index is centered on zero, with positive values indicating facilitation and negative values indicating competition. We analyzed the relationship between RII and grazing intensity (cows/ha and vegetation height) with linear regressions assuming the beta distribution following le Roux and McGeoch (2010) and Smithson and Verkuilen (2006), including pasture-type as a fixed factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This index is centered on zero, with positive values indicating facilitation and negative values indicating competition. We analyzed the relationship between RII and grazing intensity (cows/ha and vegetation height) with linear regressions assuming the beta distribution following le Roux and McGeoch (2010) and Smithson and Verkuilen (2006), including pasture-type as a fixed factor.…”
Section: Discussionmentioning
confidence: 99%
“…Of the few studies that have assessed plant interactions along stress gradients, most have only been able to compare two (high versus low) points along the gradient (Brooker et al , 2008. More studies are needed that sample entire stress gradients Michalet et al 2006;le Roux and McGeoch 2010).…”
Section: Introductionmentioning
confidence: 96%
“…This severity-interaction relationship pattern has been widely supported by empirical evidence (Callaway, 2007). However, and based on recent empirical data, other authors proposed that positive interactions may increase with environmental severity until they reach a plateau, which is also a monotonic pattern (see reviews in Kawai and Tokeshi, 2007;le Roux and McGeoch, 2010), take a hump-shaped pattern e i.e., negative interactions at both low and high levels of environmental severity and positive interactions at intermediate levels (Kawai and Tokeshi, 2007;Maestre and Cortina, 2004a,b;Michalet et al, 2006), or follow a combination of the above patterns.…”
Section: The Balance Of Planteplant Interactions Along Resource and Ementioning
confidence: 95%
“…Other studies have found that, at the stressful end of the gradient, the intensity of the positive net interaction reaches an asymptote (Kawai and Tokeshi 2007;le Roux and McGeoch 2010) or may wane and become neutral (Forey et al 2010;Maalouf et al 2012) or even negative (de Bello et al 2011;Koyama and Tsuyuzaki 2013). Some authors have proposed that the decrease in the net interaction most likely occurs because facilitators are less successful in ameliorating stress levels under very severe conditions, while competition for resources may decrease, remain constant or even increase with stress (Michalet et al 2006;Maestre et al 2009).…”
Section: Watering Treatmentmentioning
confidence: 92%